Astaxanthin as a King of Ketocarotenoids: Structure, Synthesis, Accumulation, Bioavailability and Antioxidant Properties - Anagha Nair; Ankesh Ahirwar; Shashikala Singh; Reeta Lodhi; Aishwarya Lodhi; Anshuman Rai; Dipak A Jadhav; Harish; Sunita Varjani; Gurpreet Singh; Justine Marchand; Benoît Schoefs; et al. (Marine Drugs, 2023)
Astaxanthin (3,3-dihydroxy-β, β-carotene-4,4-dione) is a ketocarotenoid synthesized by Haematococcus pluvialis/lacustris, Chromochloris zofingiensis, Chlorococcum, Bracteacoccus aggregatus, Coelastrella rubescence, Phaffia rhodozyma, some bacteria (Paracoccus carotinifaciens), yeasts, and lobsters, among others However, it is majorly synthesized by Haematococcus lacustris alone (about 4%). The richness of natural astaxanthin over synthetic astaxanthin has drawn the attention of industrialists to cultivate and extract it via two stage cultivation process. However, the cultivation in photobioreactors is expensive, and converting it in soluble form so that it can be easily assimilated by our digestive system requires downstream processing techniques which are not cost-effective. This has made the cost of astaxanthin expensive, prompting pharmaceutical and nutraceutical companies to switch over to synthetic astaxanthin. This review discusses the chemical character of astaxanthin, more inexpensive cultivating techniques, and its bioavailability. Additionally, the antioxidant character of this microalgal product against many diseases is discussed, which can make this natural compound an excellent drug to minimize inflammation and its consequences.